Diagnosis of pregnancy in bitches by transabdominal palpation along with haematological studies - Namsui Thou (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1999)
with the object of evolving a suitable and reliable method of early pregnancy diagnosis in bitch, a study was undertaken to investigate the efficacy of transabdominal palpation and~aematological profile during various stages of pregnancy in bitches. Seventeen apparently normal healthy Alsatian and 7 Pomeranian bitches aged 1~ to 6 years selected at random